Adenosine Receptor A2a, but Not A1 in the rVLM Participates Along With Opioids in Acupuncture-Mediated Inhibition of Excitatory Cardiovascular Reflexes - Malik, Shaista; Samaniego, Tracy; Guo, Zhi-Ling (Frontiers in Neuroscience, 2019)
Electroacupuncture (EA) can be used to lower high blood pressure (BP) in clinical practice. However, precise mechanisms underlying its effects on elevated BP remain unclear. Our previous studies have shown that EA at the P5-6 acupoints, overlying the median nerve, attenuates elevated BP induced by gastric distension (GD) through influence on rostral ventrolateral medulla (rVLM). Although adenosine is released during neuronal activation in the rVLM, its role in acupuncture-cardiovascular regulation is unknown. The purinergic system is involved in cardiovascular pressor and depressor responses, including via selective activation of A1 and A2a rVLM receptors, respectively. The action of A2a receptor stimulation in the central nervous system may be further regulated through an endogenous opioid mechanism. However, it is uncertain whether this putative action occurs in the rVLM. We hypothesized that adenosine in the rVLM contributes to EA modulation of sympathoexcitatory reflexes through an A2a but not an A1 adenosine receptor-opioid mechanism. EA or sham-EA was applied at the P5-6 acupoints in Sprague-Dawley male rats subjected to repeated GD under anesthesia. We found that EA (n=6) but not sham-EA (n=5) at P5-6 significantly (P<0.05) attenuated GD-induced elevations in BP. EA modulation of sympathoexcitatory cardiovascular reflexes was reversed significantly after rVLM microinjection (50 nl) of 8-SPT (10 mM; non-selective adenosine receptor antagonist; n=7) or SCH 58261 (1 mM; A2a receptor antagonist; n=8; both P<0.05), but not by DPCPX (3 mM; A1 receptor antagonist; n=6) or the vehicle (5% dimethylsulfoxide; n=6). Moreover, microinjection of an A2a receptor agonist, CGS-21680 (0.4 mM; n=8) into the rVLM attenuated GD-induced pressor responses without EA, which mimicked the EA’s inhibitory effects (P<0.05). After blockade of opioid receptors with naloxone (1 mM) in the rVLM, SCH 58261’s reversal of EA’s effect on GD-induced pressor responses was blunted, and CGS-21680-mediated inhibitory effect on pressor responses was not observed. Furthermore, neurons labeled with adenosine A2a receptors were anatomically co-localized with neurons stained with enkephalin in the rVLM. These data suggest that the involvement of rVLM adenosine A2a receptors in EA modulation of GD-induced pressor reflexes is, at least in part, dependent on the presence of endogenous opioids.